ANALISIS PERTUMBUHAN EKONOMI DAN DISPARITAS PENDAPATAN DI KABUPATEN JEMBER TAHUN 2008-2011 - Prasetyo, Davi Eko (Jurnal Ekonomi Pembangunan, 2013)
The aim of this research is to know the economic development among Districts in the Jember Regency, know each classification among Districts in the Jember Regency based Klassen Typology and know the income disparity among Districts in the Jember Regency. Analysis result using regional economic development method, shows that total of PDRB development average in the Jember Regency is 5.38% from 2008 to the 2011. Analysis result of Klassen Typology determining for 1st Classification: 1) The region develops and grows fast, in the Jember Regency, this classification contain of 8 Districts. 2) 2nd Classification: The region developed, but also depressed, in the Jember Regency, this classification contain of 3 Districts, 3) 3rd Classification: Fast developed region, in the Jember Regency, this classification contain of 12 Districts, 4) 4th Classification: Poor region, in the Jember Regency, this classification contain of 8 Districts. The result of Williamson index average number that reach the highest value is in the Mumbul Sari and Pakusari Districts. Whereas, for income disparity number or the lowest discrepancy index is in the Rambi Puji District. Thus, income disparity or discrepancy among Districts in the Jember Regency shows the index average of income disparity or economic discrepancy that really high in 2008 to the 2011.